2008
DOI: 10.1108/10650740810849061
|View full text |Cite
|
Sign up to set email alerts
|

Technology readiness, internet self‐efficacy and computing experience of professional accounting students

Abstract: ArticleTechnology readiness, internet self-efficacy and computing experience of professional accounting students Purpose -This study aims to assess the state of technology readiness of professional accounting students in Malaysia, to examine their level of internet self-efficacy, to assess their prior computing experience, and to explore if they are satisfied with the professional course that they are pursuing in improving their technology skills. Design/methodology/approach -A questionnaire was developed to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
76
1
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(88 citation statements)
references
References 10 publications
2
76
1
9
Order By: Relevance
“…Other TAM researchers have found an influence of CSE on the TAM (Chen et al, 2002;Downey, 2006;Strong et al, 2006). TAM researchers have also evaluated the influence of users' e-learning self-efficacy (Grandon, Alshare, & Kwan, 2005;Park, 2009) and internet self-efficacy (Lai, 2008;Ma & Liu, 2007) on their technology acceptance. E-learning self-efficacy refers to the personal confidence in finding information and communicating with an instructor within the e-learning system and the necessary skills for using the system.…”
Section: Usability and Technology Acceptancementioning
confidence: 95%
See 1 more Smart Citation
“…Other TAM researchers have found an influence of CSE on the TAM (Chen et al, 2002;Downey, 2006;Strong et al, 2006). TAM researchers have also evaluated the influence of users' e-learning self-efficacy (Grandon, Alshare, & Kwan, 2005;Park, 2009) and internet self-efficacy (Lai, 2008;Ma & Liu, 2007) on their technology acceptance. E-learning self-efficacy refers to the personal confidence in finding information and communicating with an instructor within the e-learning system and the necessary skills for using the system.…”
Section: Usability and Technology Acceptancementioning
confidence: 95%
“…Internet self-efficacy focuses on how one believes he/she can accomplish (i.e., establish, maintain, and utilize) the Internet now or in the future (Lai, 2008). Ma and Liu (2007) argued that Internet self-efficacy is more than a judgment of one's capability of applying internet skills; it is a measure of individual specific skills in using an Internet browser.…”
Section: Usability and Technology Acceptancementioning
confidence: 99%
“…In the discussion about the acceptance of new information and technology system, (Jaafar et al, 2007), in service provision (Lai, 2007), and in education (Lai, 2008;Lai & Chong, 2007).…”
Section: The Elaboration Above Is In Line Withmentioning
confidence: 99%
“…Public universities in Malaysia are aggressively promoting the use of web-based learning or electronic learning (e-learning) for continuous professional development and distance education [2]. Allen and Presnal reported that technology is used in education because it could improve access to education [3].…”
Section: Introductionmentioning
confidence: 99%
“…According to Ming-Ming, discomfort refers to a perceived lack of control over technology and feeling lack of confidence in using the new technologies properly [2]. The discomfort situation always linked with lack of ICT skills among learners.…”
Section: Introductionmentioning
confidence: 99%